2022
DOI: 10.1039/d2tc03053e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive photochromic and Raman dual response to ethylenediamine gas through polyoxometalate–viologen crystalline hybrid

Abstract: A new crystalline complex is successfully synthesized based on Dawson type polyoxometalate and amino substituted viologen. It exhibits ultrasensitive photochromic and Raman dual response to ethylenediamine gas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…However, in the detection of toxic amines, how to quickly and conveniently analyze and determine the category and concentration of toxic amines is still a huge challenge, and it is of great significance to human life and health and rapid treatment. In 2022, 188 Gao and co-workers synthesized and reported a class of highly sensitive POM–viologen crystalline photochromic hybrid materials with selective detection for ethylenediamine (H 2 AV)[H 2 (P 2 W 18 O 62 )]·9.5H 2 O (AV = N , N ′-bis(δ-aminopropyl)-4,4′-bipyridinium)(Fig. 18).…”
Section: Applicationsmentioning
confidence: 99%
“…However, in the detection of toxic amines, how to quickly and conveniently analyze and determine the category and concentration of toxic amines is still a huge challenge, and it is of great significance to human life and health and rapid treatment. In 2022, 188 Gao and co-workers synthesized and reported a class of highly sensitive POM–viologen crystalline photochromic hybrid materials with selective detection for ethylenediamine (H 2 AV)[H 2 (P 2 W 18 O 62 )]·9.5H 2 O (AV = N , N ′-bis(δ-aminopropyl)-4,4′-bipyridinium)(Fig. 18).…”
Section: Applicationsmentioning
confidence: 99%
“…[16][17][18][19] Previous studies also indicated that different POMs have characteristic Raman signals coming from the vibration of different M-O (M = Mo or W) bonds, which reveals that POMs can be used as inorganic Raman signal molecules. 20,21 In addition, for silver ions, they have a strong affinity for oxygen atoms, and thus they easily coordinate with surface oxygen atoms in POMs to form different crystalline compounds. 22,23 Based on the above analysis, it is assumed that if POMs directly connect with Ag + to construct 3D porous frameworks, it may present high Raman activity.…”
Section: Introductionmentioning
confidence: 99%
“…11 The photosensitizer performance of viologen-based photochromic materials can be improved by regulating their structure and composition through methods such as nitrogen substituent modification, 12,13 counteranion 14,15 and inorganic-organic hybridization. [16][17][18][19] Recently, many novel inorganic-organic hybrid crystalline materials based on viologens and transition metals 9,[20][21][22] or polyoxometalates [23][24][25] have been developed. These materials exhibit a fast response and a dense packing mode, which enables long-lifetime charge separation and stable color retention.…”
Section: Introductionmentioning
confidence: 99%